Designing 3D Biological Surfaces via the Breath‐Figure Method. Issue 6 (15th January 2018) - Chen, Shuangshuang; Gao, Su; Jing, Jiange; Lu, Qinghua
Abstract: The fabrication of biointerfaces that mimic cellular physiological environments is critical to understanding cell behaviors in vitro and for the design of tissue engineering. Breath figure is a self‐assemble method that uses water droplets condensed from moisture as template and ends up with a highly ordered hexagonal pore array; this approach is used to fabricate various biological substrates. This progress report provides an overview of strategies to achieve topographical modifications and chemical‐patterned arrays, such as modulation of the pore size, shape and selective decoration of the honeycomb holes. Using recent results in the biological fields, potential future applications and developments of honeycomb structures are commented upon. Abstract : Breath figure provides a convenient approach to fabricating the honeycomb‐like substrates with highly ordered hexagonal pore arrays. There are many strategies to functionalize the honeycomb films for biological applications, including modulating chemistry, wettability, and morphological parameters. The honeycomb films exhibit high potential in biological fields including for cell scaffold, antibacteria, bio‐macromolecule arrays, bioseparation, and biosensors.